2003
DOI: 10.1128/jcm.41.9.4217-4223.2003
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassay Targeting Nonstructural Protein 5 To Differentiate West Nile Virus Infection from Dengue and St. Louis Encephalitis Virus Infections and from Flavivirus Vaccination

Abstract: West Nile virus (WNV) is an emerging flavivirus that has caused frequent epidemics since 1996. Besides natural transmission by mosquitoes, WNV can also be transmitted through blood transfusion and organ transplantation, thus heightening the urgency of development of a specific and rapid serologic assay of WNV infection. The current immunoassays lack specificity because they are based on detection of antibodies against WNV structural proteins and immune responses to structural proteins among flaviviruses cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 17 publications
5
103
0
1
Order By: Relevance
“…[12][13][14][15] Many travelers to dengue-endemic areas receive a vaccine for YF or JE for travel to locations where they could encounter one of these flavivirus infections. Our PRNT results demonstrated false-positive anti-DENV IgM ELISA results due to crossreactivity between flaviviruses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Many travelers to dengue-endemic areas receive a vaccine for YF or JE for travel to locations where they could encounter one of these flavivirus infections. Our PRNT results demonstrated false-positive anti-DENV IgM ELISA results due to crossreactivity between flaviviruses.…”
Section: Resultsmentioning
confidence: 99%
“…Given the potential cross-reactions of dengue with other arboviral infections when tested by ELISA for anti-DENV IgM result, these samples were tested for DENV and YF by plaque-reduction neutralization test (PRNT) at the CDC Arboviral Diseases Branch according to a protocol based on WHO guidelines; PRNT for JE was planned but could not be performed. 12 Funding limited number of samples that could be confirmed by PRNT; we were not able to test samples of subjects with seroconversion of anti-DENV IgG who received JE or YF vaccines.…”
Section: Methodsmentioning
confidence: 99%
“…In general, an IgG ELISA lacks specificity within the flavivirus serocomplex groups, however it has been demonstrated that the IgG response to the prM membrane glycoprotein is specific to individual flaviviruses as no crossreactivity was observed in sera collected from individuals infected with dengue or Japanese encephalitis virus 85 . Similarly, it has been demonstrated that IgG specific for the NS5 protein can potentially discriminate between infections caused by West Nile, dengue and St Louis encephalitis viruses 86 . Finally, dengue-specific IgG was shown to have high specificity in an assay using a recombinant polypeptide located in the N-terminal region of the envelope protein 87 .…”
Section: Igg Elisamentioning
confidence: 98%
“…The fact that NS5 is a reliable serological marker of WNV infection (Wong et al, 2003) suggests that further investigation of immunodominance of the epitopes identified here during human and animal infections is warranted.…”
Section: Discussionmentioning
confidence: 99%